A multicenter feasibility study on ultrafiltration via a single peripheral venous access in acute heart failure with overt fluid overload. (1st August 2017) - Morpurgo, Marco; Pasqualini, Mario; Brunazzi, Maria Cristiana; Vianello, Gabriele; Valle, Roberto; Roncon, Loris; Fiorini, Fulvio; Aspromonte, Nadia; Barbiero, Mario; Goldoni, Marco; Marenzi, Giancarlo
Abstract: Objectives: The need for a central venous catheter has limited the widespread use of ultrafiltration in daily clinical practice for the treatment of acute heart failure (AHF) with overt fluid overload. We evaluated the feasibility of a new ultrafiltration device, the CHIARA (Congestive Heart Impairment Advanced Removal Approach) system, that utilizes a single-lumen cannula (17G, multi-hole) inserted in a peripheral vein of the arm. Methods: In this multicenter, prospective, feasibility study, consecutive ultrafiltration treatments (lasting ≥ 6 hours and with an ultrafiltration rate ≥ 100 ml/h) with the CHIARA device and a single peripheral venous approach were performed at 6 Italian hospitals. For each session, we evaluated the performance of the venous access, the ultrafiltrate volume removed, and the cause of its interruption. Results: One-hundred-three ultrafiltration sessions were performed in 55 patients with AHF (average 1.9 ± 1.7 treatment/patient). The overall median length of ultrafiltration treatment was 14 h (interquartile range 7–21) with removal of 3266 ± 3088 ml of fluid (183 ± 30 ml/hour). The treatment was successfully completed in 92 (89%) sessions and in 80% of patients. The mean suction flow rate from the vein was 70 ± 20 ml/min, while the mean re-injection flow rate was 98 ± 26 ml/min. There were no clinically relevant complications related to the venous access and/or to the anticoagulant therapy with heparin. Conclusions: The study demonstrated that the CHIARA system satisfies clinical applicability and efficacy criteria in the treatment of AHF, in terms of adequate fluid removal through a single peripheral venous access.